PENGARUH KINERJA KEUANGAN DAN TAX MANAGEMENT TERHADAP FINANCIAL DISTRESS DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI - Ghanny, Margarita (Jurnal Penelitian Akuntansi (JPA), 2024)
This research aims to test and obtain empirical evidence regarding the influence of financial performance and tax management on financial distress with leverage as a moderating variable. The independent variables used in this research are financial performance and tax management. Meanwhile, the moderating variable used in this research is leverage, as well as the dependent variable used in this research, namely financial distress as measured by the Altman z-score. The samples collected and used were secondary data from the financial reports of companies in the Food and Beverage Consumer Goods Industry Sector which were available on the official website of the Indonesia Stock Exchange from 2018-2022, totaling 215 pieces of data. The technique for collecting samples applies the purposive sampling method and is analyzed using the logistic regression method with the help of STATA software. The results of this study show that financial performance has no effect on financial distress, tax management has a negative effect on financial distress, leverage as a moderating variable is proven not to be able to weaken the negative effect of the relationship between financial performance and financial distress, leverage as a moderating variable is proven to weaken the negative effect of the relationship between tax management and financial distress